Formulasi gel ekstrak daun kelor (Moringa oleifera Lam.) serta uji karakteristik sediaan dan uji cemaran mikrobiologi - Dewi, Asiska Permata; Fadila, Sarah; Darmadi, Darmadi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Moringa leaves are a type of medicinal plant that contains flavonoids, polyphenols, saponins, and tannins. The objective of this research is to make a Moringa leaf extract gel formulation and test the characteristics of the preparation's and test for microbial contamination. The characteristics are tested using organoleptic tests, pH, homogeneity, spreadability, and dosage form consistency. Meanwhile, the microbiological contamination testing included the Total Plate Count and Yeast Mold Count tests. The results of testing the characteristics of the preparation on Moringa leaf extract gel, in the organoleptic test revealed that the dosage form was semi-solid, the color was white to brownish yellow, and the odor of the extract, the pH of the preparation ranged between 6-6.2, spreadability ranged from 6.2-6.4 cm, consistency of the preparation was homogeneous, and no phase separation occurred. Furthermore, the ALT test at concentrations of 2%, 4%, 6%, 8%, positive control, and negative control obtained a colony count of 9.5x106 CFU/mL. 3.8x105 CFU/mL, 6.7x106 CFU/mL, 6.8x105 CFU/mL, 1.47x104 CFU/mL and 1x101 CFU/mL. Meanwhile, the AKK test obtained colony counts of 1.35x105 CFU/mL, 9.7x102 CFU/mL, 1.1x102 CFU/mL, 7.8x103 CFU/mL, 1x101 CFU/mL, and 1x101 CFU/mL. According to the findings of the ALT test, the number of bacterial colonies still surpasses the threshold standards stipulated by BPOM number 32 of 2019. Meanwhile, the AKK test showed that the concentration of 2% exceeds the limit for yeast mold contamination